Pemilihan alternatif pengolahan air lindi untuk TPA Nusa Lembongan, Bali dengan proses hierarki analitik (AHP) - Farhan Hadi Siregar; Muhammad Jatmoko; Aulia Risky Adinda; Rika Chairani Dalimunthe; Mega Mutiara Sari; I Wayan Koko Suryawan (Jurnal Pengelolaan Lingkungan Berkelanjutan (Journal of Environmental Sustainability Management), 2023)
The waste generated in Nusa Lembongan is processed by open dumping. Open dumping tends to have a negative impact on the environment, one of which is leachate. The leachate will have an impact on the surrounding ecosystem if it is not safe. Treatment can be applied in various ways, one of which is a waste stabilization pond, but this technology will not be enough to add further treatment. The purpose of this study is to determine the appropriate treatment technology for further treatment of leachate at the Nusa Lembongan TPA. This research uses literature study and analytic hierarchy process for decision analysis. There are three alternatives given, namely biofilter, wetland, and anaerobic baffle reactor (ABR). The criteria used are cost estimation, land area, and BOD allowance, alternative use of ABR has the highest weight value compared to the other two technologies. This is because ABR requires a low land area compared to the other two alternatives. This fits with the limited land available in Nusa Lembongan.